Supplementation of natural minerals on the performance of broiler - Ahamed, Z; Das, SC; Dey, B; Azad, MR; Islam, KMS (Bangladesh Journal of Animal Science, 2020)
An experiment was conducted to evaluate the efficacy of AZOMITE® as source of natural minerals on growth performance of commercial broiler. A total of 1,020 day-old Cobb 500 male broiler chicks were randomly allocated to 5 dietary treatments with 6 replications per treatment having 34 chicks in each pen. The five dietary treatments were: (i) basal diet without AZOMITE®, (ii) basal diet with 0.25% AZOMITE®, (iii) basal diet with 0.50% AZOMITE® which was recommended by manufacturer, (iv) basal diet with 0.75% AZOMITE® and (v) basal diet with 1.0% AZOMITE®. Broilers were reared in open-sided gable type house for a period of 32 days. Results showed that the supplementation of AZOMITE® had significant effect on growth performance (p<0.01) of broilers. Live body weight (LBW), body weight gain (BWG), average daily gain (ADG), feed intake (FI), feed conversion ratio (FCR), European efficiency factor (EEF) and gain cost of the birds fed various levels of AZOMITE® were significantly improved as compared to the control. Meat characteristics results indicated that the treatments had no significant effect on dressing percent, thigh, drumsticks and breast percentage among the dietary groups. Taken together, it may be concluded that the supplementation of AZOMITE® in commercial broiler at 0.50 to 1.0% improved live weight, feed intake and feed conversion ratio of commercial broilers. Bang. J. Anim. Sci. 2019. 48 (2): 92-98